Encapsulation of CO2 into amorphous alpha-cyclodextrin powder at different moisture contents – Part 1: Encapsulation capacity and stability of inclusion complexes. (15th July 2016) - Ho, Thao M.; Howes, Tony; Bhandari, Bhesh R.
Highlights: Crystallization of amorphous α-CD during complexation increased complexed CO2 ratio. Water amount inducing crystallization of amorphous CO2 -α-CD were 13–17% MC (w.b.). CO2 encapsulation capacity by this method was over 1 mol CO2 /mol α-CD. Crystallization of amorphous α-CD during complexation increased complex stability. Abstract: This study investigated the effects of water-induced crystallization of amorphous alpha-cyclodextrin (α-CD) powder on CO2 encapsulation at 0.4–1.6 MPa pressure for 1–72 h through the addition of water (to reach to 13, 15 and 17% wet basis, w.b.) into amorphous α-CD powder prior to the encapsulation. The results showed that the α-CD encapsulation capacity was over 1 mol CO2 /mol α-CD after pressurizing for longer than 48 h. The encapsulated CO2 concentration by the addition of water was considerably higher ( p  < 0.05) than that of amorphous α-CD powder (5.51% MC, w.b.) without an addition of water and that of crystalline α-CD powders under the same MC and encapsulation conditions. A comparison of CO2 release properties (75% relative humidity, 25 °C) from complexed powders prepared from amorphous and crystalline α-CD powders under the same conditions is also presented.